Accreditation from a positive leadership perspective - Tosheska Trajkovska, Katerina (My University, 2022)
When lab staff is alone—no management or official representatives in sight—one of the things they complain about the most is accreditation. At worst, we consider it a huge waste of time and effort. It’s not that we don’t see the benefits of accreditation. We do. But we find that these returns do not satisfy us and are definitely not worth the costs associated with the process. So if accreditation is unlikely to go away, is it possible to make lemonade out of this lemon and create a more positive outcome from what appears to be long-lasting,exhausting and sometimes boring process? House cleaning If we take the perspective, “If we have to do it anyway, how can we make it better? we could start by saying that accred- itation gives us a rather rare opportunity to do some cleaning in the labs. By forcing us to regularly review our policies and procedures and the staffing of various tasks in our laboratories, we have an externally imposed reason to engage in a process that can lead to internally beneficial outcomes. Become proactive Just as we have learned to be more proactive when we conduct laboratory evaluations—not only evaluating past per- 17 formance, but also building on the past to set goals for the future—accreditation can help us become more proactive. Accreditation offers us a regular opportunity to ask ourselves where we want to go based on where we have already been. It gives us a chance to plan systematically by looking at our best practices and comparing our current results with those of the past. Meeting the enemy We are the ones who vote to approve, adopt or accept the standards. We may have met the enemy - and that is us. If some of us who feel constrained by outdated standards and processes used by accrediting agencies were a little more open in our meetings about why accreditation often hurts us more than it helps, maybe we could start to initiate some change. If we don’t succeed, at least we wouldn’t be worse off than we are now.
Keywords: accreditation; leadership